2020
DOI: 10.3390/atmos11040374
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Electronic Cigarette (e-cigs) Refill Liquids Prior to EU Tobacco Product Directive Adoption: Evaluation of BTEX Contamination by HS-SPME-GC-MS and Identification of Flavoring Additives by GC-MS-O

Abstract: The present study focused on the determination of benzene, toluene, ethylbenzene and xylenes (BTEX) concentration levels in 97 refill liquids for e-cigs selected by the Italian National Institute of Health as representative of the EU market between 2013 and 2015 prior to the implementation of the European Union (EU) Tobacco Product Directive (TPD). Most of the e-liquids investigated (85/97) were affected by BTEX contamination, with few exceptions observed (levels below the limit of quantification (LOQ) of head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The higher odds of stroke in dual smokers suggest that e-cigarettes may have an additive effect on traditional smokers. The additive effect may be attributed to e-cigarette ingredients other than nicotine, like carbonyls, including aldehydes such as formaldehyde, acetaldehyde, and acrolein; fine and ultrafine particulate matter (PMs); benzene; toluene; ethylbenzene; and xylenes (BTEX) [8,[20][21][22][23]. Parekh et al also found higher odds of stroke among the young adult population (18-44 years) secondary to the additive effect of e-cigarettes (aOR: 2.91) on current or former traditional smokers (sole combustible cigarette OR: 1.83), without establishing a relationship between sole e-cigarette use and stroke [5].…”
Section: Discussionmentioning
confidence: 99%
“…The higher odds of stroke in dual smokers suggest that e-cigarettes may have an additive effect on traditional smokers. The additive effect may be attributed to e-cigarette ingredients other than nicotine, like carbonyls, including aldehydes such as formaldehyde, acetaldehyde, and acrolein; fine and ultrafine particulate matter (PMs); benzene; toluene; ethylbenzene; and xylenes (BTEX) [8,[20][21][22][23]. Parekh et al also found higher odds of stroke among the young adult population (18-44 years) secondary to the additive effect of e-cigarettes (aOR: 2.91) on current or former traditional smokers (sole combustible cigarette OR: 1.83), without establishing a relationship between sole e-cigarette use and stroke [5].…”
Section: Discussionmentioning
confidence: 99%
“…These samples are often diluted and injected directly [ 11 , 12 ]. In the case of gas chromatography (GC) and the analysis of volatile organic compounds (VOC), the use of headspace (HS) sampling [ 13 , 14 ] or solid phase microextraction (SPME) [ 15 ] is also quite common.…”
Section: Introductionmentioning
confidence: 99%
“…This paper is related to the preparation of TD-GC×GC calibration samples using a liquid standard mixture containing 48 VOC. The following three techniques were studied and compared: the first one, the simplest, is the manual deposit (MD) of the calibration solution directly on the head of the tube; the two other techniques were gas stream assisted deposit (GSAD) [1,[9][10][11], and vaporization followed by adsorption assisted by gas stream (VGSD) [6,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%